Respuesta :
The following steps of solving for the roots of 2x² - 4x -3 = 0 were retrieved from another source
Step 1 2x² - 4x = 3
Step 2 2(x² - 2x) = 3
Step 3 2(x² - 2x + 1) = 3 + 1
Step 4 2(x - 1)² = 4
From this, we can see that on Step 3, Tran made a mistake of adding 1 to 3. As we can see, 2(x² - 2x + 1) = 2x² - 4x + 2. That means, instead of adding 1, it should have been 2.
Therefore, the step that Tran first made an error is Step 3.
The solution to the quadratic equation 2x² - 4x - 3 = 0 is given as x = 1 ± √5/2
What is an equation?
An equation is an expression that shows the relationship between two or more numbers and variables.
Given the quadratic equation:
2x² - 4x - 3 = 0
Using completing the square, add 3 to both sides:
2x² - 4x - 3 + 3 = 0 + 3
2x² - 4x = 3
Divide through by the coefficient of x²:
x² - 2x = 3/2
Add to both sides the square of half the coeficient of x:
x² - 2x + 1 = 3/2 + 1
(x - 1)² = 5/2
x = 1 ± √5/2
The solution to the quadratic equation 2x² - 4x - 3 = 0 is given as x = 1 ± √5/2
Find out more on equation at: https://brainly.com/question/2972832
#SPJ5